Immunisations and antibiotics in patients with anterior skull base cerebrospinal fluid leaks. Issue 7 (14th July 2014) - Rimmer, J; Belk, C; Lund, V J; Swift, A; White, P
Abstract Objective: There are no UK guidelines for the use of antibiotics and/or immunisations in patients with an active anterior skull base cerebrospinal fluid leak. This study aimed to define current UK practice in this area and inform appropriate guidelines for ENT surgeons. Method: A web-based survey of all members of the British Rhinological Society was carried out and the literature in this area was reviewed. Results: Of those who responded to the survey, 14 per cent routinely give prophylactic antibiotics to patients with cerebrospinal fluid leaks, and 34.9 per cent recommend immunisation against at least one organism, most commonly Streptococcus pneumoniae (86.7 per cent). Conclusion: There is no evidence to support the use of antibiotic prophylaxis in patients with a cerebrospinal fluid leak. We propose that all such patients are advised to seek immunisation against pneumococcus, meningococcus and haemophilus.